Electronic Wallet as a Multi Payment Media Solution in the Industrial Revolution Era 4.0: Study on FEBI Students IAIN Sultan Amai Gorontalo, Indonesia - Sofhian, Sofhian; Da'aliwa, Mirsa Gulam (Talaa : Journal of Islamic Finance, 2021)
In line with technological development, all forms of community activity have now shifted to digitalization, including payment activities. The purpose of this research is to examine and describe whether server-based electronic wallets can be a solution for multi-payment media in the era of the industrial revolution 4.0 for millennial and what electronic wallets better support the needs of multi-payment in the era of industrial revolution 4.0. The method used by the researcher in this research is the descriptive qualitative method. Data collection techniques used are interviews, observation, and documentation. In this study, the data obtained were analyzed using a phenomenological approach which was collected, reduced, presented, and then given a conclusion. The results of this study are that at FEBI IAIN Gorontalo there are 695 students of which 158 students use electronic wallets or about 22.73%. In use, electronic wallets can already be their multi-payment media solution in the era of the industrial revolution 4.0 because of the convenience factor where students can make various payments using smartphones, fast because payments are made only by scanning a QR code, economical because admin fees are cheap and free as well as lots of promos. , flexible because it can be used anywhere and under any conditions, safe to lose money and avoid theft and supervised by Indonesian Bank